The Role of Learning Media Through Citizenship Education Approach at School Base - Nurhalimah (International Journal of Students Education, 2024)
Research purposes this is for develop potential learning civics for students educate school basic. This research use method literature review. Data in this study obtained through technique data collection in the form of a framework, concept or orientation for do analysis or classification facts collected in research conducted from sources reference (books, journals, papers). Functions of learning media hold very important role. A number of types of learning media that can be used developed and implemented in the learning process Civics are 1) Visual Media, 2) Audiovisual Media, and 3) Multimedia. Learning media no only just complement to the learning process but also one of the factor determinant the success of the learning process in the classroom. Selection the right type of learning media can make it easier transfer material from teacher to students, so that the learning process become more effective and efficient. Learning media no only impact on development cognitive student but also helps develop imagination and skills. Fifth function the describe impact positive learning media towards the learning process. Learning media have a number of function including communication, motivation, meaningfulness, equality perception, and responding individuality.